Si waveguide polarisation rotation chirped Bragg grating. Issue 2 (1st January 2017) - Okayama, H.; Onawa, Y.; Shimura, D.; Yaegashi, H.; Sasaki, H.
Abstract : Polarisation independent silicon waveguide wavelength filter using Bragg grating with chirped period is reported. The polarisation rotation and filter peak with wide flat top response is obtained. An antisymmetric grating structure and rib waveguide is used. We experimentally obtained polarisation independent flat‐top band‐pass filter consisting of polarisation beam splitter (PBS) and Bragg grating.